2006
DOI: 10.1542/peds.2004-2880
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Community-Based Trial of Home Visiting to Reduce Blood Lead Levels in Children

Abstract: Until a reservoir of lead-safe housing is created, programs that educate families to reduce environmental exposure are needed. Although providing families with quantitative information regarding lead contamination may have a role in short-term efforts to prevent lead exposure, these null findings suggest that it has little benefit once BLLs are elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…10 A scan of the literature reveals clinical trials of home visiting models focused on: birth outcomes, 11,12 immunization rates, 13 emergency department visits, 13 prenatal care, 14 breastfeeding, 15 accidental injury, 12,16 child maltreatment, 17 children' s dietary practices, 18 and lead levels. 19 Although models differ, most home visiting models have a structured protocol, materials, and goals and use a combination of direct information sharing or service provision and case management with referral to community resources. 20 Most address child health and development by targeting parenting; for example, encouraging sensitive caregiving, increasing parent knowledge on development, or recognizing child illnesses.…”
Section: What Is Home Visiting?mentioning
confidence: 99%
“…10 A scan of the literature reveals clinical trials of home visiting models focused on: birth outcomes, 11,12 immunization rates, 13 emergency department visits, 13 prenatal care, 14 breastfeeding, 15 accidental injury, 12,16 child maltreatment, 17 children' s dietary practices, 18 and lead levels. 19 Although models differ, most home visiting models have a structured protocol, materials, and goals and use a combination of direct information sharing or service provision and case management with referral to community resources. 20 Most address child health and development by targeting parenting; for example, encouraging sensitive caregiving, increasing parent knowledge on development, or recognizing child illnesses.…”
Section: What Is Home Visiting?mentioning
confidence: 99%
“…Environmental lead exposure occurs predominantly by ingestion of lead-contaminated household dust or soil in older houses that contain leadbased paint; the degree of exposure often increases with deterioration or renovation of the houses. Smelters and tap water are two other important potential sources of lead exposure (Brown et al, 2006). The current screening threshold established by the Centers for Disease Control and Prevention for an elevated blood lead level in a child is 10 µg/dl (Bellinger, 2004), but this value should not be interpreted as a level below which adverse effects do not occur.…”
Section: Introductionmentioning
confidence: 99%
“…Bloodlead levels of children were not followed in this study and actual impact is difficult to determine. However, as mentioned before, studies have found that even control groups that only receive pamphlets or flyers on lead prevention show some meaningful reduction in blood-lead levels [21].…”
Section: Discussionmentioning
confidence: 85%
“…Well-designed programs have been shown to be effective at reducing blood-lead levels for young children anywhere from 1 lg/dl to 5 lg/dl. In general, these successful lead intervention programs have been grassroots programs with nurses and community members conducting repeated door-to-door education meetings and demonstration with residents [19][20][21][22]. Studies have found that the majority of the blood-lead level reduction typically occurs in the first three to 6 months of a program and even control groups that only receive pamphlets or flyers show some meaningful reduction in blood-lead levels [21].…”
Section: Introductionmentioning
confidence: 99%